Metal Halide Perovskite Surfaces with Mixed A‐Site Cations: Atomic Structure and Device Stability. (29th December 2022) - Hieulle, Jeremy; Son, Dae‐Yong; Jamshaid, Afshan; Meng, Xin; Stecker, Collin; Ohmann, Robin; Liu, Zonghao; Ono, Luis K.; Qi, Yabing
Abstract: Mixing cations in the perovskite structure has been shown to improve optoelectronic device performance and stability. In particular, Csx MA1‐x PbBr3 (MA = CH3 NH3 ) has been used to build high‐efficiency light‐emitting diodes. Despite those advantages, little is known about the exact location of the cations in the mixed perovskite film, and how cation distribution affects device properties and stability. By using scanning tunneling microscopy, the exact atomic structure of the mixed cation Csx MA1‐x PbBr3 perovskite interface is revealed. In addition, X‐ray photoelectron spectroscopy, ultraviolet photoemission spectroscopy and inverse photoemission spectroscopy are used to study the stability and electronic properties of the Csx MA1‐x PbBr3 perovskite film. Partial substitution of MA + by Cs + induces a modification of the perovskite surface structure, leading to improved device stability is shown. These results provide a better understanding of the key parameters involved in the stability of mixed cation perovskite solar cells. Abstract : The perovskite interface has a strong influence on perovskite solar cell device performance, and determination of the exact perovskite surface structure is of vital importance for more accurate band structure calculations. Herein, the impact of A‐site cation mixing on the perovskite surface atomic structures and its correlation with higher device stability are studied by scanning tunneling microscopy and photoemission spectroscopy.